Caring for Democratic Attitudes and Behavior Through Political Education - Handitya, Binov (Law Research Review Quarterly, 2018)
Democracy in Indonesia can be seen as a mechanism and ideals of life of the Unitary Republic of Indonesia. The journey of democracy in Indonesia cannot be separated from the role and support of Pancasila which is considered to have a very important role for every element that grows in this country. The Pancasila which we have agreed upon as the philosophy of national life (Philosophy Grondslag) and the ideology of the Indonesian people is able to provide the confidence of this nation to continue to exist until now. The Indonesian people have always consistently applied the value of Pancasila in a simple, dynamic way and not only applied in a state context. At the village community level, they are familiar with the teachings of genuine Indonesian democracy. For example, village deliberation activities have given us the view that we have a native culture of the nation such as holding meetings to reach consensus, mutual cooperation, holding protests against the arbitrariness of leaders and opposing excessive power. In upholding the principle of democracy as a system of social life is very dependent on the elements that support democracy itself. At present the relevant elements in upholding democracy are the concept of the rule of law, civil society, political infrastructure and a free and responsible press. However, there are other ways to care for the principle of democracy so that it can provide benefits to the lives of the Indonesian people, namely through Political Education.